Epidemiology of Adult Soft-Tissue Sarcomas in Germany. (4th April 2018) - Saltus, Catherine W.; Calingaert, Brian; Candrilli, Sean; Lorenzo, Maria; D'yachkova, Yulia; Otto, Thorsten; Wagner, Uwe; Kaye, James A.
Abstract : We conducted a retrospective cohort study using data compiled from the regional German cancer registries by the Centre for Cancer Registry Data (ZfKD) at the Robert Koch Institut (RKI) to describe the epidemiology of adult soft-tissue sarcomas (STS) in Germany in 2003–2012, focusing on advanced STS. We identified 33, 803 incident adult cases of STS (other than the Kaposi sarcoma and gastrointestinal stromal tumors). The incidence of STS was 6.05 (95% confidence interval (CI), 5.82–6.29) per 100, 000 in 2012 (4, 079 cases). During 2003–2012, the most common histologic categories were leiomyosarcoma (19%), liposarcoma (16%), and STS not otherwise specified (14%). The overall STS-specific mortality rate in 2012 was 2.31 (95% CI, 2.06–2.57) per 100, 000, and the median overall survival from initial diagnosis was 5.83 (95% CI, 5.50–6.08) years. Using STS mortality rates as a proxy for incidence of advanced STS in Germany and applying the age- and sex-specific rates to the corresponding German population, we estimated that 1, 581 incident adult advanced STS cases occurred in Germany in 2012. Our findings contribute to a refined understanding of the population burden of STS in Germany, including the number of patients with advanced STS who may be candidates for systemic treatment.